Theory and Experiment for Wireless-Powered Sensor Networks: How to Keep Sensors Alive - Kae Won Choi; Rosyady, Phisca Aditya; Ginting, Lorenz; Aziz, Arif Abdul; Setiawan, Dedi; Dong In Kim (IEEE transactions on wireless communications, 2018)
In this paper, we investigate a multi-node multi-antenna wireless-powered sensor network (WPSN) comprised of one power beacon and multiple sensor nodes. We have implemented a real-life multi-node multi-antenna WPSN testbed that operates in real time. We propose a beam-splitting beamforming technique that enables a power beacon to split microwave energy beams toward multiple nodes for simultaneous charging. We experimentally demonstrate that the beam-splitting beamforming technique achieves the Pareto optimality. For perpetual operation of the sensor nodes, we adapt an energy neutral control algorithm that keeps a sensor node alive by balancing the harvested and consumed power. The joint beam-splitting and energy neutral control algorithm is designed by means of the Lyapunov optimization technique. In our experiments, the proposed algorithm has successfully kept all sensor nodes alive by optimally splitting energy beams toward multiple sensor nodes.